FUNGSIONALIZATION OF ACETOPHENONE USING SECONDARY AMINE CATALYSED BY COPPER (II) - Mujiati, Wiwin
The ?-amino carbonyl is f ound in many medicinal compounds, so an ef f icient synthetic method to obtain this ?-amino carbonyl needs to be developed. One of the drugs that is synthesized through ?-amino carbonyl derivatives is salbutamol, a drug commonly used in treating asthma. In this study, the results of the ?-carbon f unctionalization reaction of carbonyl compounds in the form of acetophenone derivatives and secondary amines were reported using a copper (II) bromide catalyst. The reaction product was purif ied b y chromatography and analyzed spectroscopically using Nuclear Magnetic Resonance (NMR). The reaction product between acetophenone (2a) and morpholine (3) with copper (II) bromide catalyst produces a ketoamide compound, namely 1-morpholino-2-phenyletane-1,2-di-on (4a) with a yield of 6%. The structure of these compounds was conf irmed by 1D (1H and 13C) and 2D (HMBC and HSQC) NMR measurements. The discovery of the ketoamide synthesis method w ith a simple reaction is an important discovery because ketoamide compounds are also an important part of various bioactive compounds. The presence of hydroxy, ac etate and benzyloxy groups on the acetophenone aromatic ring causes the reaction not to take p lace.